Efeito do enriquecimento ambiental e da lesão do cortéx pré-frontal medial nos níveis de ansiedade-traço e -estado - Goes, Tiago Costa (2016)
Effect of environmental enrichment and lesion of the medial prefrontal cortex in the trait and state anxiety levels. Tiago Costa Goes, Aracaju – SE, 2016. In the study of anxiety, there are two distinct concepts: state and trait anxiety. State anxiety is the anxiety a subject experiences at a particular moment in time, it is transitory and may be affected by external stimuli; whereas trait anxiety is considered an enduring feature of an individual, it is relatively stable over time and a predisposing factor for anxiety disorders. Despite its relative stability, in animals, trait anxiety seems to be sensitive to the influence of environmental enrichment established after weaning. Whether this influence also occurs when the enrichment is established in adulthood is still unknown. The brain structures implicated in trait anxiety are also unknown, but scientific evidences point to the medial prefrontal cortex (mPFC) Thus, the aims of this study were: 1) evaluate the effect of environmental enrichment in the levels of trait anxiety and state anxiety of adult rats (Experiment I); and 2) evaluate the effect of lesion of the mPFC in the levels of trait anxiety and state anxiety of adult rats (Experiment II). As, by definition, trait anxiety modulates state anxiety, this was also evaluated. In Experiment I, seventy adult Wistar male rats were first tested in the free-exploratory paradigm (FEP – animal model of trait anxiety) in order to be categorized according to their levels of trait anxiety (high, medium and low). Subsequently, half of the animals from each category returned to their home cages (standard condition) and the other half was transferred to an enriched environment (enriched condition). After three weeks, all animals were again tested in FEP. Seven to 10 days later, 50 of the 70 animals were tested on the elevated plus-maze test (EPM – animal model of state anxiety). The data from FEP were analyzed using ANOVA and Tukey's post hoc test, while the data from EPM were analyzed using Student‟s t test. In FEP, environmental enrichment reduced locomotor activity independently of the anxiety category and, it decreased the levels of trait anxiety of highly anxious rats. In EPM, no effect of environmental enrichment was observed in the levels of state anxiety. In Experiment II, 66 adult Wistar male rats were first tested in FEP and categorized according to their levels of trait anxiety. Three to six days after this exposure, all animals were submitted to stereotaxic brain surgery. Half of the animals from each anxiety category was allocated to the mPFC-lesioned group and the other half to the Sham-lesioned group. After seven to nine days, all animals were again tested in FEP. Eight to 10 days later, the animals were tested in the hole board test (HB – animal model of state anxiety). The data from both FEP and HB were analyzed using ANOVA and Tukey's post hoc test. In FEP, the mPFC lesion, independently of the anxiety category, increased locomotor activity in the second exposition to FEP in relation to first exposition to FEP and it decreased levels of trait anxiety of highly anxious rats. In HB, the mPFC lesion reduced the state anxiety of the animals of all anxiety categories. Thus, this study showed that the environmental enrichment, established in adulthood, was able to was able to decrease the trait anxiety levels without affecting the levels of state anxiety, whereas the lesion of the CPFM decreased both levels trait anxiety and state anxiety of adult Wistar rats.